General Anaesthesia and Emergency Surgery in Heart Transplant Recipient - Farshid Ejtehadi; Sharon Carter; Lucy Evans; Mubashar Zia; Howard Bradpiece (Case Reports in Surgery)
The number of patients who undergo heart transplant is increasing. Due to surgical emergencies, many of those may require general anesthesia in hospitals where subspecialized anesthetists may not be available. We present a case of a male patient who had heart transplant and required general anesthesia for emergency appendicectomy. Physiology of the heart after transplant, preoperative considerations, and postoperative monitoring has been discussed in our report.